Twelfth night, or, What you will - Shakespeare, William, 1564-1616 (Mumbai : Wilco International, 2023)
Named for the twelfth night after Christmas, the end of the Christmas season, Twelfth Night plays with love and power. The Countess Olivia, a woman with her own household, attracts Duke (or Count) Orsino. Two other would-be suitors are her pretentious steward, Malvolio, and Sir Andrew Aguecheek. Onto this scene arrive the twins Viola and Sebastian; caught in a shipwreck, each thinks the other has drowned. Viola disguises herself as a male page and enters Orsinos service. Orsino sends her as his envoy to Oliviaonly to have Olivia fall in love with the messenger. The play complicates, then wonderfully untangles, these relationships.
Keywords: Shipwreck survival -- Drama; Siblings -- Drama